FILOGENIA Y BIOGEOGRAFÍA DE CUBADRILUS (OLIGOCHAETA: OCTOCHAETIDAE), UN GÉNERO NUEVO DE LOMBRIZ DE TIERRA DE CUBA - Rodríguez Aragonés, Carlos; Fragoso, Carlos (Instituto de Ecología, A.C., 2002)
The finding of three new Cuban earthworm species, made it neccesary to describe Cubadrilus gen.nov. in order to include these species and former Cuban Zapatadrilus species. A parsimony phylogenetic analysis (PAUP, v. 3.1.1.) of the genera Cubadrilus, Zapatadrilus, Trigaster, Borgesia and Neotrigaster supported this arrangement, and pointed out the following synapomorphies of Cubadrilus gen. nov: spermathecal duct elongated and joined to anterior septum, half-ring shaped spermathecal diverticula and ventral bifid oesophagous invaginations. The new genus Cubadrilus is considered an intermediate taxon between the mexican Zapatadrilus and the other genera of the Greater Antilles. On the basis of recent interpretations of the geologic history of Cuba, it is proposed that the ancestors of Cubadrilus dispersed from Southern North America during the tertiary.